Pengembangan Media Pembelajaran E-Comic pada Mata Pelajaran PAI Kelas VII SMP - Busro, Fauziah Salsabil; Hendri, Nofri; Novrianti, Novrianti; Kurnia, Reni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to produce a valid and practical product in the form of an E-Comic for the PAI subject in the 7th grade of junior high school so it can be used in learning. This type of research is Research and Development (R&D) using the 4D development model, which consists of the stages of define, design, development, and disseminate. Data collection is conducted through observations, interviews, questionnaires, and documentation. The results of product development are obtained through validation and practicality testing. The results of product development are obtained through validity and practicality tests. The validity test was carried out by 3 validators, namely 2 media validators and 1 material validator. In the first stage, the average percentage of the two validators was 87.1% and the average percentage of 90% of the two validators in the second stage, both of which were categorized as “Very Valid”. Then, the average percentage of expert validators on the first and second day was 93.3% and 97.8% which were categorized as “Very Valid”. The practicality test of e-comic media conducted on seventh grade students of SMP Negeri 1 Solok is 87.9% and falls into the “Very Practical” category. Based on the validity and practicality tests, e-comic in learning Islamic Religious Education class VII SMP is valid and practical for use in learning.